Bragg Grating Packages With Nonuniform Dimensions for Strain and Temperature Sensing - Mokhtar, M. R.; Sun, T.; Grattan, K. T. V. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2012)
This paper presents a novel approach to better reducing the dimensions of sensor packages for specific applications to enable the simultaneous measurement of strain and temperature using fiber Bragg grating (FBG)-based sensors. This approach is demonstrated through comparing three packaging designs, in which there is either a nonuniform height or width to vary the response of two co-located FBGs to strain and temperature. In this way, the measurement of the shift in their respective Bragg wavelengths will allow the accurate determination of both the strain and temperature from their dissimilar strain and temperature coefficients. In addition to providing the necessary protection for the sensors, this type of packaging design also allow better control over the differences between the coefficients thus, in turn, maximizing the sensitivity to which strain and temperature values can be determined.